An Experimental Study for Determination of Convective Heat Transfer Coefficients on Yarn Production Line - Patkavak, Mert; Demir, Hakan (AMER INST PHYSICS, 2020)
In this study, the convective heat transfer coefficient around small diameter circular wires is determined in an effort to obtain main parameters affecting quenching in melt fiber spinning The different diameter wires and air velocities were employed for detailed research in parallel and cross flow by using a wind tunnel. These correlations were based on conditions used in monofilament yarn production line. The wire diameters which are used in the experiments were varied from 0,2 mm to 1 mm and air velocities were varied from 0,5 m/s to 5m/s. These wires were heated with power supply and cooled with specified air flows for the determination of convective heat transfer coefficients. A multimeter was used to measure the voltage and current values; and the resulting wire resistances were calculated for each wire surface temperature. The convective heat transfer coefficients were obtained from total electrical power consumption and formulas of convection heat coefficient and radiative heat transfer. The experiments were carried out with different Reynolds numbers. Finally, the resulting Nusselt correlations were compared to the correlations reported by Ohkoshi Glicksman, Copley, Kase and Matsuo, Churcill and Bernstein, Hilpert, Fand and Kesvani, and, Dito. The present results are in good agreement with literature and they are in the same range for these Reynolds numbers.
Keywords: Physics; Polymer Science